Long-term field experiments carried out in savannas and hillsides agroecosystems by Soil Physics (PE-2: Soils project of CIAT) - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
The soil physics (PE-2: Soils project of CIAT) had several field experiments in both tropical savannas and hillsides agroecosystems. To organize the data, three big blocks were established: one block for hillsides agroecosystem and two blocks (Culticore and Plains (Altillanura)) for savannas agroecosystem. For hillsides agroecosystem, data from 1995 to 2000 were organized systematically. For savannas, data from 1993 to 1999 were completed.